Optimal Tax Rate for Maximal Revenue Generation - Ridley, Dennis; Davison, Cartreal (Technium Social Sciences Journal, 2022)
Tax revenue is a function of tax rate. As tax rate increases tax revenue increases, peaks, and then falls. This paper presents an empirically observed relationship between corporate income tax rates and tax revenues. Infrastructure plays a critical role in economic growth and development. Infrastructures such as public facilities that include endogenous capital stock of knowledge, machines, computers, recordings, etc. are commonly the result of government investments. Money for these investments is obtained from tax revenues. One such tax is corporate income tax. The tax rate that corresponds to maximum revenue from taxes is determined to be 32%. It is proposed that this is a false optimum as the preferred objective should be to maximize economic growth where the corresponding maximizing rate is 26%.